Per capita rice consumption in Bangladesh: Available estimates and IFPRI’s validation survey results - Yunus, Mohammad; Rashid, Shahidur; Chowdhury, Sulin (International Food Policy Research Institute, 2019)
Accuracy of rice consumption estimates varies considerably, depending on the data source and survey techniques. Therefore, the report first compiles estimates of per capita daily consumption available from different published and unpublished sources. The accrued data were compared in conjunction with the ones found from a small validation survey conducted by the IFPRI-led JV in the summer of 2018. The methodology of the validation survey drew on strategies adopted by other nationally representative surveys, specifically the Household Income and Expenditure Survey (HIES) conducted by the Bangladesh Bureau of Statistics (BBS), and IFPRI’s own Bangladesh Integrated Household Survey (BIHS). Simultaneously, it employed a two-step approach for critically assessing the original survey instruments in contrast to the current consumption behaviors with rapid appraisal. The validation survey established pertinent findings related to changes in the per capita consumption assessments when new elements were incorporated. Addition of new hypotheses based on the consumption of rice and rice products outside the home provides a spin on the per capita consumption estimates generated by the validation survey. Overall, the review, assessment of alternative estimates, and results of this validation survey seek to aid the construction of significant strategic policy decisions related to the demand-supply balance of rice in the country.